Parasitismo de Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae) em diferentes hospedeiros e cores de cartelas - Magalhães, G. O. [UNESP]; Goulart, R. M. [UNESP]; Vacari, A. M. [UNESP]; Bortoli, S. A. de [UNESP] (Instituto Biológico, 2012)
Species of the Trichogramma genus are the most studied and used natural enemies worldwide. The quality and performance of the mass-produced control agents can be influenced by some factors such as the choice of the appropriate host for multiplication of the parasitoid and the use of different colors of cards, given that these parasitoids may use physical stimuli such as color to help in locating the host. The aim of the present study was to evaluate the influence of color cards on the parasitism of Trichogramma pretiosum in eggs of Anagasta kuehniella and in eggs of two populations of Plutella xylostella, one reared on broccoli, the other on collard greens. Hosts' eggs were stuck to the different color cards. The selected colors were blue, yellow, green, pink, red and black. For every treatment, 20 replications were observed, and each was composed by 30 eggs of those hosts. Later the cards were exposed to parasitoid females individually in Eppendorf® tubes of 2.0 mL containing one honey droplet for feeding for 24 hours. The number of parasitized eggs and the emergence percentage were evaluated. The strain Tp-8 of T. pretiosum presented better greater parasitism in A. kuehniella eggs. The feeding substratum of P. xylostella (collard greens and broccoli) did not influence the parasitism of T. pretiosum. Thus for mass rearing of T. pretiosum, blue, green and white color cards are most suitable.

Espécies do gênero Trichogramma são dos inimigos naturais os mais estudados e utilizados atualmente no mundo. A qualidade e o desempenho desses agentes de controle produzidos massalmente podem ser influenciados por alguns fatores, tais como a escolha do hospedeiro adequado para multiplicação do parasitoide e a utilização de diferentes cores de cartelas, haja vista que estes parasitoides podem utilizar estímulos físicos como cor para facilitar a localização do hospedeiro. O objetivo desse trabalho foi avaliar à influência de cores de cartelas no parasitismo de Trichogramma pretiosum que foi submetido a ovos do hospedeiro alternativo Anagasta kuehniella e duas populações de Plutella xylostella, sendo uma delas criada no substrato brócolis e a outra em couve. Ovos dos hospedeiros foram aderidos às cartelas de papel cartão, sendo que as cores selecionadas foram: azul, amarela, verde, rosa, vermelha e preta. Para cada tratamento foram observadas 20 repetições, cada uma composta por 30 ovos dos hospedeiros. Posteriormente, as cartelas foram expostas às fêmeas do parasitoide individualizadas em tubos tipo Eppendorf® de 2,0 mL que continha uma gotícula de mel para alimentação delas por 24 horas, em teste de confinamento. Foram avaliados o número de ovos parasitados e a porcentagem de emergência. A linhagem Tp-8 de T. pretiosum apresentou maior parasitismo em ovos de A. kuehniella. Os substratos de alimentação de P. xylostella (couve e brócolis) não influenciam o parasitismo de T. pretiosum. As cores de cartelas indicadas para a condução da criação massal de T. pretiosum são azul, verde e branco.
Influence of color cards, hosts and first trophic level on Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae) parasitism
Keywords: Parasitoide de ovos; Criação massal; Controle biológico; Egg parasitoids; Mass rearing; Biological control